Pengembangan Pembelajaran Berbasis Autoplay Media Studio 8 Pada Mata Pelajaran Marketing SMK Negeri 2 Blitar - Djoko Dwi Kusumajanto; Dewi Ayu Utami (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2021)
Autoplay Media Studio 8 software aims to create an interactive learning media by using a presentation integrated with video, sound, images, flash, and text on the basic competencies of Goods and Services Marketing Strategy Implementers. The goal author aims by conducting this research is to ascertain the feasibility of learning media as a marketing subject for class X students of online business and marketing. Method used for this research is development model Research and Development which also commonly known as educational research and development. Several steps included within research and development method are recognizing problems and potential, data collection, designing product, designing validation, designing revision, testing product in trial, producing revision, user trial, product revision, and mass product. To validate data for this questionnaire, the author used Likert scale. The research shows a sign that the development of instructional media got positive results. Autoplay Media Studio 8 Software allure student’s interest and simplify the way student tries to understand presented material. DOI: https://dx.doi.org/10.17977/UM014v14i12021p71